Leadership for Collective Learning: A Distributed Perspective - Salleh, Hairon; Wee Pin, Goh Jonathan (International Business Education Journal, 2015)
Over the last decade or so, distributed leadership has gained increasing attention in education. It has been claimed that distributed leadership, in its different patterns of distribution, have valued-added effects on school effectiveness, remains to be intuitively attractive, compelling and positive, and is endorsed by many as good practice. Its prominence is due to educational contexts that are increasingly getting complex insofar as the changes accompanying educational reforms are characterized by increasing intensity, rapidity, fluidity and uncertainty. Schools are now expected to deliver diverse curricular experiences towards a wider set of learning outcomes to satisfy broader school stakeholders’ needs. School leadership, which has traditionally been within the realm of the school principal and her management team (usually, department and level heads), is placed under great strain, especially that which pertains to maintaining practices to support teaching and learning. This most likely explains why over time practices on instructional leadership has been delegated, shared or distributed to teachers not in the management team. The close links between distributed and instructional leadership is therefore understandable – the result of which is the rise of teacher leadership. This paper presents a theoretical frame on collective learning for teacher leadership which can cut across different contexts within the school organization. The central argument is for teacher leadership to support collective learning for instruction. The conclusion highlights four research gaps pertaining to this central argument.